Policy determinants of physical activity across the life course: a 'DEDIPAC' umbrella systematic literature review. (18th October 2017) - Puggina, Anna; Aleksovska, Katina; Buck, Christoph; Burns, Con; Cardon, Greet; Carlin, Angela; Chantal, Simon; Ciarapica, Donatella; Condello, Giancarlo; Coppinger, Tara; Cortis, Cristina; D'Haese, Sara; et al.
Abstract: Background: Despite the large number of studies and reviews available, the evidence regarding the policy determinants of physical activity (PA) is inconclusive. This umbrella systematic literature review (SLR) summarizes the current evidence on the policy determinants of PA across the life course, by pooling the results of the available SLRs and meta-analyses (MAs). Methods: A systematic online search was conducted on MEDLINE, ISI Web of Science, Scopus and SPORTDiscus databases up to April 2016. SLRs and MAs of observational studies investigating the association between policy determinants of PA and having PA as outcome were considered eligible. The extracted data were assessed based on the importance of the determinants, the strength of evidence and the methodological quality. Results: Fourteen reviews on 27 policy determinants of PA were eligible for this umbrella SLR. The majority of the reviews were of moderate quality. Among children, a clear association between time spent outdoors and PA emerged. Among adults, working hours were negatively associated with PA, though evidence was limited. At the population level, community- and street-scale urban design and land use policies were found to positively support PA levels, but levels of evidences were low. Conclusions: With this umbrella SLR the policy determinants of PA at individual-level and population-level have been summarized and assessed. None of the investigated policy determinants had a convincing level of evidence, and very few had a probable level of evidence. Further research is needed, preferably by using prospective study designs, standardized definitions of PA and objective measurement of PA.